Application of a Dielectric Measurement Technique for Calculating Water Loss from Two Texture-contrasting Soils Grown with Upland Rice - Bandi Hermawan; Pajrina Pajrina; Sumardi Sumardi; Indra Agustian (TERRA : Journal of Land Restoration, 2018)
Most of the water loss from the soil profile occurred through the evapotranspiration process especially when the plant covers were under maximum growth periods.  This study aimed to apply a technique of measuring a dielectric variable for calculating soil water content and crop water use in the coarse and medium textured soils grown with upland rice.  A couple of wires were inserted into the soil repacked in a 10-kg polybag grown with upland rice, the electrical impedance representing the dielectric value was measured using an instrument called the impedance meter.  The impedance values were converted into the soil water content using a nonlinear regression model of ? = a.ebZ where a and b were constants.  Results showed that the proposed technique of measuring the electrical impedance has successfully been applied to calculate the soil water content and the water use by upland rice grown in loamy sand and sandy loam soils.  Cumulative water loss from loamy sand was about 4 L plant-1 higher for the coarse loamy sand in the first 30 days of a measurement period, but about 10 L plant-1 higher for finer sandy loam on the 90th day of the rice growth period.  Higher biomass of upland rice in the sandy loam soil could increase the evapotranspiration rates and be the main reason for higher water use in this soil.